THE DEVELOPMENT OF AN INSTRUCTIONAL MODEL FOR ENHANCING PROBLEM SOLVING AND MATHEMATICAL CONNECTIONS SKILLS OF THE FIFTH GRADE STUDENTS - Mirasingha, Narin (Academic Journal Phranakhon Rajabhat University, 2024)
The objectives of this research are to: 1) develop and test the effectiveness of a teaching model to promote problem-solving skills and mathematical connections among 5th-grade elementary school students, 2) study the effectiveness of using this teaching model, and 3) study the students’ satisfaction towards the teaching model. The sample group consists of 32 fifth-grade elementary school students in the second semester of the academic year 2023 from Warin Wischachat Municipal School, Education Division, Warin Chamrap Municipality. The tools used include 1) a learning management plan, 2) problem-solving and mathematical connection skills assessment, 3) learning effectiveness assessment test, and 4) satisfaction assessment form. The data analysis involves finding the mean and standard deviation, conducting non-independent tests, and content analysis of the research results. The study found that: 1) the teaching model aimed at promoting problem-solving skills and mathematical connections among fifth-grade elementary school students comprises five components: 1) principles, 2) objectives, and 3) learning management processes with five steps: (1) reviewing prior knowledge, (2) learning new content, (3) practicing, (4) evaluating performance and reflection, and (5) applying the knowledge. 4) measurement and evaluation, and 5) factors supporting learning management, including social systems, response principles, and support systems. 2) The results of comparing problem-solving skills and mathematical connections before and after using the teaching model showed that the skills were significantly higher after learning than before learning at the statistical significance level of .05, and 3) the study also found that student satisfaction with the teaching model was at the highest level.